2007
DOI: 10.1016/j.vaccine.2007.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intranasal administration of a truncated NS1 modified live influenza virus vaccine in swine

Abstract: In the U.S., despite available swine influenza virus (SIV) vaccines, multiple influenza subtypes as well as antigenic and genetic variants within subtypes continue to circulate in the swine population. One of the challenges to control and eliminate SIV is that the currently used inactivated influenza virus vaccines do not provide adequate cross-protection against multiple antigenic variants of SIV in the field. We previously generated a recombinant H3N2 swine influenza virus (SIV) based on the influenza A/SW/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(137 citation statements)
references
References 45 publications
(52 reference statements)
7
127
1
2
Order By: Relevance
“…Previous work showed that intranasal NS1 126 TX98 elicited significant IgG and IgA antibody titers in lungs, and the vaccine protected pigs against challenge with TX98 or a similar H3N2 strain [21]. In that study, NS1 126 TX98 vaccination conferred partial protection against the heterosubtypic IA04 challenge.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previous work showed that intranasal NS1 126 TX98 elicited significant IgG and IgA antibody titers in lungs, and the vaccine protected pigs against challenge with TX98 or a similar H3N2 strain [21]. In that study, NS1 126 TX98 vaccination conferred partial protection against the heterosubtypic IA04 challenge.…”
Section: Discussionmentioning
confidence: 66%
“…Pigs were euthanized and necropsied 5 days post challenge. Bronchoalveolar lavage fluid (BALF) was collected for virus titration as described previously, using 50 ml Minimum Essential Medium per lung lavage [21]. Viral titers were analyzed in nasal swab and BALF samples by a standard tissue culture infectious dose assay on MDCK cell monolayers.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The A/Swine/IA/00239/2004(H1N1) clusters within the b H1 swine IAVs (Lorusso et al, 2011). This virus was selected because it has been fully characterized, genetically and antigenically (Anderson et al, 2015), and it has been used in several pathogenesis (Vincent et al, 2007) and transmission studies Diaz et al, 2013;Romagosa et al, 2011). The challenge virus was 91.5 and 73.7 % identical at the nucleotide level to the H1 c and d vaccine virus strains, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it was shown that SIVs generated by genetic modifications within the hemagglutinin (HA) or nonstructural (NS) genes are attenuated in pigs (12,13). These viruses demonstrated the ability to induce strong cell-mediated and humoral immunity and to provide full protection against homologous SIVs and partial protection against heterologous SIVs (11,(14)(15)(16)(17). In this study, we describe a novel approach that generates a LAIV candidate containing an H3 subtype of HA derived from a circulating SIV in the genetic background of H1N1 SIV.…”
mentioning
confidence: 99%